Investigation of properties of soils stabilised with groundnut waste - O. Adunoye, G.; O. Osineye, T.; C. Ezeh, H. (International Journal of Physical Research, 2022)
Improvement of soil strength has gained a wider and increasing acceptance in civil engineering applications. This study therefore investigat-ed the effects of coarse content of groundnut shell ash on the properties of selected lateritic soils. To achieve the aim of the study, soil sam-ples were collected from two identified active borrow pits. The following geotechnical tests were conducted on the soil samples in their natural state, using standard procedures: natural moisture content, specific gravity, grain size analysis, Atterberg limits, compaction and California bearing ratio. Subsequently, the soils were treated with coarse content (part retained on 425 Âµm BS sieve) of groundnut shell ash at 2 %, 4 % and 6 % proportions by weight of dry soil. Results showed that the degree of laterisation is high in the two soil samples, having specific gravity values of 2.84 and 2.72 respectively. Results of Atterberg limit tests and grain size analysis showed that the soils belong to A-2-7 using AASHTO classification system. 6 % groundnut shell ash gave the lowest plasticity index for first sample, while 2 % ground-nut shell ash gave the lowest plasticity index for second sample. Also, 2 % groundnut shell ash gave the lowest optimum moisture content for first sample, while 6 % groundnut shell ash gave the lowest optimum moisture content for the second sample. Similarly, 2 % groundnut shell ash gave the highest maximum dry density for first sample, while 4 % groundnut shell ash gave the highest maximum dry density for second sample The California bearing ratio reached a maximum value of 4 % at 6 % groundnut shell ash, for first sample; it increased to 14 % at 2 % groundnut shell ash, for second soil sample. The study concluded that lateritic soils can be modified with coarse component of groundnut shell ash.Â Â